Bilateral pediatric myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) optic neuritis: a case report - Ahmad Fauzi, Nadhirah; Abd Bari, Muhd Syafi; Rosli, Abdul Hadi; Wan Mahmud Sabri, Wan Muhammad Najib; Jabbari, Aidila Jesmin (Springer Nature, 2024)
Optic neuritis (ON) is defined as an acquired disorder of the optic nerve that may be associated with demyelinating diseases or infectious or inflammatory processes. In children, the manifestation of this condition differs from that in adults, where it typically presents with bilateral papillitis subsequent to a preceding viral illness. Nonetheless, the main concern for practitioners is the possibility of its conversion to multiple sclerosis (MS). In recent years, there has been increased awareness regarding differentiating MS from other demyelinating ON phenotypes, namely, neuromyelitis optica spectrum disorder (NMOSD) and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD). Despite the clinical similarities among these three entities, they vary in terms of pathophysiology, clinical course, treatment approaches, and prognostication. In this paper, we highlight the case of a child with MOGAD ON who was clinically severe at presentation and has typical features of ON and the appropriate investigation and treatment done to achieve complete visual recovery.